The initial deposit decision and the occurrence of bank runs - Johan de Jong (Tinbergen Institute, 2021)
In studies of bank runs the initial deposit decision is typically not taken into account. However, it is unlikely that people will entrust money to a bank that they expect to fail in the near future. The aim of this study is to investigate to what extent this mechanism prevents bank runs. It introduces an experiment in which participants first have to choose if they want to receive their endowments as a deposit in a `risky' bank that pays a high interest or a `safe' bank that pays a lower interest. After this decision they can withdraw the money from their account or leave it in to receive the interest. The availability of different deposit options leads to a very clear theoretical prediction: all choose to deposit in the risky bank with the high interest rate and consequently leave the deposit in the bank. In the experiment the first prediction is not confirmed: almost half of the participants choose to deposit in a safer alternative. However, in contrast to the control treatment in which participants are not offered a choice, only very few of those that choose the risky bank withdraw their deposits later.
Keywords: G21; G40; E71; D81; 330; Bank runs; Initial deposit decision; Experimental economics; Coordination games